PENGARUH NAPTHALENE ACETIC ACID (NAA) DAN BENZYL ADENINE (BA) TERHADAP KEBERHASILAN SETEK DAN PERTUMBUHAN ANAKAN Sansevieria aubrytiana ‘Tiger Stripe’ - Saputri, Rahmi; Nurhidayah, Tengku; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sansevieria is a horticultural plant species origin from Africa, Arab and Indonesia. Sansevieria has economic value and good prospects. These opportunities should must be balanced with plant propagation. Propagation by cuttings of plants with growth regulators to support growth. The research aims is to know the effect of NAA, BA and both combination that supports the growth of Sansevieria aubrytiana cuttings. This research was conducted in the Screen House, Plant Laboratory Faculty of Agriculture, University of Riau, from September 2013 to March 2014. This research was conducted experimentally completely randomized design (CRD) with 5 treatments, with 3 replications. Data were analyzed of variance followed by Duncan's new multiple range test level of 5%. Parameters observed were percentage of live cuttings, rooted cuttings percentage, the percentage of cuttings formed tillers and number of tiller. The results showed no effect of growth regulators on the success of cuttings and seedlings growth of Sansevieria aubrytiana. Keywords: Sansevieria, Cuttings, PGR.